Suspect and non-targeted screening of chemicals of emerging concern for human biomonitoring, environmental health studies and support to risk assessment: From promises to challenges and harmonisation issues - Pourchet, Mariane; Debrauwer, Laurent; Klanova, Jana; Price, Elliott J; Covaci, Adrian; Caballero-Casero, Noelia; Oberacher, Herbert; Lamoree, Marja; Damont, Annelaure; Fenaille, François; Vlaanderen, Jelle; Meijer, Jeroen; et al. (Environment international, 2020)
Large-scale suspect and non-targeted screening approaches based on high-resolution mass spectrometry (HRMS) are today available for chemical profiling and holistic characterisation of biological samples. These advanced techniques allow the simultaneous detection of a large number of chemical features, including markers of human chemical exposure. Such markers are of interest for biomonitoring, environmental health studies and support to risk assessment. Furthermore, these screening approaches have the promising capability to detect chemicals of emerging concern (CECs), document the extent of human chemical exposure, generate new research hypotheses and provide early warning support to policy. Whilst of growing importance in the environment and food safety areas, respectively, CECs remain poorly addressed in the field of human biomonitoring. This shortfall is due to several scientific and methodological reasons, including a global lack of harmonisation. In this context, the main aim of this paper is to present an overview of the basic principles, promises and challenges of suspect and non-targeted screening approaches applied to human samples as this specific field introduce major specificities compared to other fields. Focused on liquid chromatography coupled to HRMS-based data acquisition methods, this overview addresses all steps of these new analytical workflows. Beyond this general picture, the main activities carried out on this topic within the particular framework of the European Human Biomonitoring initiative (project HBM4EU, 2017-2021) are described, with an emphasis on harmonisation measures.
Keywords: Biological Monitoring; monitorování životního prostředí; lidé; Environmental Health; Suspect screening; Chromatography, Liquid; High resolution mass spectrometry; Non-targeted screening; Environmental Pollutants; biologický monitoring; Environmental Monitoring; environmentální zdraví; vystavení vlivu životního prostředí; Biomonitoring; látky znečišťující životní prostředí; Metabolites; Environmental Exposure; chromatografie kapalinová; Chemical of emerging concern; Humans